Academics’ profile and perceived institutional leadership practices in public and private universities - Abdullah, Norazharuddin Shah; Azman, Norazian Mohmad; Ghani, Erlane; Muhammad, Kamaruzzaman; Ilias, Azleen; Jais, Ismie Roha Mohamed (Edelweiss Applied Science and Technology, 2023)
This study analyses the profiles of academics and their perceived institutional leadership practices at their universities. A questionnaire survey was conducted among 1771 academics from Malaysian public and private universities. The results of the survey show that women make up the majority of academics in universities, and most of them hold at least a master's degree. The academics at the universities have an average of more than six years of professional experience, and most of them are senior lecturers and associate professors. Many of the professors are or have been in senior positions. The study also shows that the majority of academics believe that the selection of senior staff at their universities is well controlled and that procedures are followed. Their universities also offer a talent pool system for institutional leaders. Academics are selected as institutional leaders on a rotational basis, and their appointment is duly publicized. However, the results of this study show that many universities continue to appoint and nominate future leaders under the old system rather than the new system. The study also shows that academics, whether from public or private universities, have similar views on the procedures of institutional leadership in their respective universities. The academics are generally in favor of the institutional governance approaches at their universities. The results of the study may be valuable in planning talent management for younger members of the academic community, as succession planning requires early intervention rather than identifying key leaders without a focus on talent management.